2010
DOI: 10.1111/j.1755-0998.2009.02754.x
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of insemination success in yellow dung flies using competitive PCR

Abstract: In spite of considerable interest in postcopulatory sexual selection, separating the effects of sperm competition from cryptic female choice remains difficult because mechanisms underlying postcopulatory processes are poorly understood. One methodological challenge is to quantify insemination success for individual males within the sperm stores of multiply mated females to discover how insemination translates into eventual paternity. Any proposed method must be applicable in organisms without extensive DNA seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 58 publications
(128 reference statements)
1
63
1
Order By: Relevance
“…Theoretical work and laboratory studies suggest that females could bias paternity toward certain males by differentially storing sperm from different males in each spermatheca and subsequently choosing sperm (or a sperm mix) from a particular spermatheca (Hellriegel and Ward 1998;Hellriegel and Bernasconi 2000;Bussière et al 2010). The present study revealed that sperm mixtures differ in wild yellow dung flies, as we found a significantly lower number of ejaculates in the singlet spermatheca compared with the doublet spermathecae.…”
Section: Discussioncontrasting
confidence: 34%
See 2 more Smart Citations
“…Theoretical work and laboratory studies suggest that females could bias paternity toward certain males by differentially storing sperm from different males in each spermatheca and subsequently choosing sperm (or a sperm mix) from a particular spermatheca (Hellriegel and Ward 1998;Hellriegel and Bernasconi 2000;Bussière et al 2010). The present study revealed that sperm mixtures differ in wild yellow dung flies, as we found a significantly lower number of ejaculates in the singlet spermatheca compared with the doublet spermathecae.…”
Section: Discussioncontrasting
confidence: 34%
“…After taking samples out of the thermocycler we again shook them carefully and spun them down, stored the plate at 4°C for 10-20 h and froze it at -20°C for at least 24 h before DNA extractions were used for subsequent processing. DNA template amount (1 ll), total PCR reaction volume (6 ll), and cycling parameters (number of cycles: 27) for the heads were the same as in Bussière et al (2010).…”
Section: Dissectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although (as expected) females showed a greater preference to oviposit on north slopes as ambient temperature increased, they found no evidence that females biased paternity towards certain male genotypes depending on the offspring's microclimate. Bussière et al (2010) used molecular techniques to demonstrate that although the mean proportion of sperm stored in the spermathecae match the published mean average paternity for the last male (the P 2 value), sperm from different males are not stored randomly across the female's sperm stores (see also Otronen et al 1997;Hellriegel and Bernasconi 2000). The mean number of ejaculates stored also differs across spermathecae (Demont et al 2011.…”
Section: Studies On Sperm Selection By Femalesmentioning
confidence: 92%
“…Any of these processes could act to bias sperm use. In some insects, the female preferentially places a certain male's sperm in an advantageous position within the sperm storage organs (Bloch Qazi 2003;Bussiere et al 2010). These dynamic sperm movements might be influenced, in some part, by male seminal proteins or the morphology of sperm themselves, but it is also likely that muscle contractions and active movements within the female tract are important factors that facilitate such movement.…”
Section: Discussionmentioning
confidence: 99%